PENGARUH KOMUNIKASI ANTARPRIBADI PEKERJA SOSIAL DAN ANAK JALANAN TERHADAP KEMANDIRIAN DAN KECERDASAN EMOSIONAL ANAK JALANAN - Sabar Riyadi (Indonesian Journal of Social Work, 2022)
Interpersonal communication is important for building our self-concept, self-actualization, and for survival. Likewise, interpersonal communication between social workers and street children will affect the survival of street children which is indicated by the level of independence and emotional intelligence of street children. The independence of street children refers to the desire to compete with others, the ability to make decisions, their self-confidence, and being responsible for what street children do and emotional intelligence refers to the ability of street children to control themselves, socialize indicated by sensitivity, caring, behaving. positive and participatory. This study aims to obtain an overview of: The effect of interpersonal communication between social workers and street children on the independence of street children, The influence of interpersonal communication between social workers and street children on emotional intelligence, The influence of interpersonal communication between social workers and street children on the formation of independence and emotional intelligence of street children. In this study using a survey method, the population of this study were street children who were fostered by the Bahtera Bandung Foundation, amounting to 451 people, using a stratified random sampling technique. The validity test used in this study was to use the product moment correlation technique. using the Internal Consistency analysis method with the Cronbach alpha coefficient test technique. Data collection techniques used in this study are: Questionnaire, Observation, Documentation Study. In testing the research hypothesis used statistical tests using Path Analysis. This research was conducted at the Bina Sejahtera Foundation (Bahtera) in Bandung. The results of the study that 1) interpersonal communication has a positive and significant influence on the independence of street children with a path coefficient of 0.509. These results indicate that the better interpersonal communication consisting of the dimensions of openness, empathy, supportive attitude, positive attitude and equality, the higher the independence of street children. 2) Interpersonal communication has a positive and significant influence on the emotional intelligence of street children with a path coefficient of 0.629. This finding shows that the better interpersonal communication which consists of the dimensions of openness, empathy, supportive attitude, positive attitude and equality, the higher the emotional intelligence of street children.